Advances in cancer research. - Vande Woude, George F.; Klein, George, 1925-2016 (Academic Press, 2006)
The Advances in Cancer Research series provides invaluable information on the exciting and fast-moving field of cancer research. This volume presents outstanding and original reviews on a variety of topics including NY-ESO-1: review of an immunogenic tumor antigen; Order, disorder, death: lessons from a superorganism; Control of differentiation in progression of epithelial tumors; Cancer vaccines: preclinical studies and novel strategies; Clinical results of vaccine therapy for cancer: learning from history for improving the future; Immunodominance and immunodomination: critical factors in developing effective CD8+ T-cell based cancer vaccines; NK cell receptors as tools in cancer immunotherapy; Innate immune recognition and suppression of tumors; Inhibitors of the HSP90 molecular chaperone: current status.